Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1080/15332748.2013.951254
|View full text |Cite
|
Sign up to set email alerts
|

The History Labs: Integrating Primary Source Literacy Skills into a History Survey Course

Abstract: In this case study, a special collections librarian and a history instructor partner to develop a series of cumulative exercises teaching primary source literacy skills for a small history survey course. This sequence of lab sessions is implemented to improve student performance in the history survey and to test this pedagogical approach. Assessment tools such as rubrics, observation, and reflective journals revealed a clear improvement in students' aptitude for a wide range of skills. The author discusses opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The author concluded that "the cumulative skill development gained as part of the laboratory approach to learning history, resulted in a positive effect on student comprehension and production in the survey course." 66 In their 2014-2015 article series Morris, Weiner, and Mykytiuk studied the concept of archival literacy, which is related to, but distinct from, the broader concept of primary source literacy. These articles presented findings from a two-phase study of the archival competencies that history students at Purdue University (phase 1) and at a representative sample of 100 higher education institutions (phase 2) were expected to possess upon graduation.…”
Section: Teachingmentioning
confidence: 99%
“…The author concluded that "the cumulative skill development gained as part of the laboratory approach to learning history, resulted in a positive effect on student comprehension and production in the survey course." 66 In their 2014-2015 article series Morris, Weiner, and Mykytiuk studied the concept of archival literacy, which is related to, but distinct from, the broader concept of primary source literacy. These articles presented findings from a two-phase study of the archival competencies that history students at Purdue University (phase 1) and at a representative sample of 100 higher education institutions (phase 2) were expected to possess upon graduation.…”
Section: Teachingmentioning
confidence: 99%
“…These sets revolve around the ability for users to: conceptualize; find and access; read, understand, and summarize; interpret, analyze, and evaluate; and use and incorporate primary sources. A number of research projects have been taken on by archivists, special collections librarians, and faculty to investigate the application and efficacy of primary source literacy in the classroom (Carini, 2009;Bahde, 2013;Horowitz, 2015;Hauck & Robinson, 2018;Quill et al, 2019). Primary source literacy activities and projects take many forms, but often involve the pairing of primary sources, at the collection or item level, with relevant curricula through site visits, classroom activities, targeted assignments, etc.…”
Section: Primary Source Literacymentioning
confidence: 99%
“…They compiled a list of eight skills to be learned, which would reappear in a more succinct form in the Guidelines (Bahde, 2013). The impetus for these labs was the history instructor's concern over previous poor student performance on final papers, and Bahde was pleased to conclude that "student performance on their final papers indicates that a skills-based laboratory approach positively affects student achievement" (Bahde, 2013). Bahde would then go on to co-edit a book on the subject, Using Primary Sources: Hands-On Instructional Exercises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this case study, Bahde and a history instructor partnered to develop a series of cumulative exercises that taught primary source literacy to students in a history survey course. They compiled a list of eight skills to be learned, which would reappear in a more succinct form in the Guidelines (Bahde, 2013). The impetus for these labs was the history instructor’s concern over previous poor student performance on final papers, and Bahde was pleased to conclude that “student performance on their final papers indicates that a skills-based laboratory approach positively affects student achievement” (Bahde, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%